Alagille syndrome and deletion of 20p. Issue 12 (December 1990) - Anad, F; Burn, J; Matthews, D; Cross, I; Davison, B C; Mueller, R; Sands, M; Lillington, D M; Eastham, E
Abstract : We add five cases of 20p deletion to the 10 cases already published. Four had craniofacial, vertebral, ocular, and cardiovascular features of Alagille syndrome, which adds weight to the assignment of this disorder to the short arm of chromosome 20. Included in our series is the first report of familial transmission of a 20p deletion.